Executive summary: African climate processes, actors and institutions: What this means for farmers - Eastern Africa Famers Federation (2023)
This document summarizes the EAFF report on 'African climate processes, actors and institutions: What this means for farmers.' The overall objective of the study is to outline and unpack climate change processes and identify important actors and institutions at national, regional, and global levels and their specific roles in curbing climate change. This study is aimed to establish how farmers’ organizations can engage, collaborate, build partnerships, cooperate, and act with synergy in promoting awareness and recognition of farmers issues. This is needed to prioritize climate change, to improve climate-resilient agricultural systems for the livelihoods of farmers amidst a changing climate, as well as to find opportunities to enhance climate finance and capacity development support.